Sorption isotherm modeling of “gaplek” flour fortified by protein from red bead tree flour - Margareta Novian Cahyanti; Alvama Pattiserlihun (Journal of Science and Science Education, 2018)
The objective of the study is to determine the characteristic of moisture sorption isotherm from "gaplek" flour fortified with protein from red bead tree flour using various modeling and being observed from the monolayer moisture content and its absorption types. This research used 5 salt solutions and storage temperature of 298K, 308K, and 318K. The models used were Brunauer-Emmet-Teller (BET), Guggenheim-Anderson-de Boer (GAB) and Caurie model. The monolayer moisture content was around 5.07 – 8.53% db. kb value of GAB model was around 0.5941-0.6252. c value of GAB model was around 16.0588-23.4111. C value of BET was around 32.7241-306.5000. Whereas the c value in Caurie model was around 1.1419-1.2769. The equilibrium and monolayer moisture content on ‘gaplek" flour fortified with protein from red bead tree flour was decreasing as the temperature going up. GAB constant value indicated that the process of moisture absorption on the "gaplek" flour fortified with protein from red bead tree flour categorized in type II.